A longitudinal study of the relationship between intimate partner violence and postpartum unsafe sex among newly diagnosed HIV-infected South African women. Issue 6 (3rd June 2019) - Reyes, H. Luz McNaughton; Maman, Suzanne; Groves, Allison K.; Moodley, Dhayendre; Chen, May S.
ABSTRACT: HIV-positive women who engage in postpartum unsafe sex are at risk for sexually transmitted infection (STI), unintended pregnancy, and secondary transmission of HIV to uninfected partners. One factor that may increase risk for postpartum unsafe sex among HIV-positive women is intimate partner violence (IPV) victimization; few studies, however, have examined this association. This longitudinal study examined whether patterns of psychological, physical, and sexual IPV, assessed during pregnancy, predicted unsafe sex at 14 weeks postpartum among South African women diagnosed as HIV-positive during pregnancy ( n  = 561). In a latent class analysis, we identified three distinct patterns of IPV victimization: non-victims (74%), moderate IPV (20%), and multiform severe controlling IPV (5%). Compared to non-victims, victims of multiform severe controlling IPV were significantly more likely to engage in postpartum unsafe sex ( p  = .01), even after adjusting for potential confounding factors. Moderate IPV was not associated with postpartum unsafe sex. Findings support the need for targeted sexual risk reduction interventions for HIV-positive pregnant women who have experienced severe patterns of IPV.